Inhibition properties of TRITON-X-100 on ferritic stainless steel in sulphuric acid at increasing temperature - Fuchs-Godec, Regina (Acta chimica slovenica, 2009)
The inhibiting action of a non-ionic surfactant of the TRITON-X series (TRITON-X-100) on stainless steel type X4Cr13 in 1.0 M H2SO4 solution at five different temperatures was investigated by the potentiodynamic polarisation measurements. The inhibition efficiency has been calculated in the presence and in the absence of the inhibitor. The experimental data suggest that the inhibition efficiency increases with increasing concentration of the TRITON-X-100, and decreases with the increasing temperature. Adsorption of the non-ionic surfactant used here obeys the Flory- Huggins isotherm. The thermodynamic parameters, such as, the heat of adsorption, adsorption entropy, and the adsorption free energy, have been calculated by employing thermodynamic equations. Kinetic parameters, also been evaluated.
Keywords: fizikalna kemija; nerjavno jeklo; potenciometrija; površinsko aktivne snovi; triton